A Multimodal Analysis of Qawwali - Iram Amjad (Linguistics and Literature Review, 2017)
This study explores qawwali from emotional, aesthetic as well as devotional aspects to get its true feel. The purpose is to trace the extent to which qawwali acts as a catalyst for ecstatic or trance-like states of spiritual experience. A multimodal framework for analysis was used to study the common emerging patterns like love of God and His last prophet Muhammad (P.B.U.H), beatitudes of God and paradox of spiritual or worldly love. The qawwali sung at the three famous shrines of Lahore, Pakistan was the main source of data. To trace its impact, perceptions of devotees were taken into account in the form of 16 case studies. It was found that qawwali’s emphatic rhythmical stress patterns repeating God’s name stirred devotees’ emotions for spiritual self-repositioning. But words fall short to capture these spiritual emotions. Hence, this study only described the emotions supposedly gaining spiritual proximity with God.